Standar Akuntansi Keuangan untuk Pengelolaan Lingkungan di Sektor FMCG: Kajian PSAK yang Relevan - Fety Widianti Aptasari; Putri, Baiq Krisnina Maharani; Khairul, Mujahidi (Jurnal Ilmiah Wahana Akuntansi, 2024)
The Fast-Moving Consumer Goods (FMCG) industry faces major challenges related to plastic waste, resource consumption, and carbon emissions. With the increasing global awareness of sustainability, FMCG companies are encouraged to transform through the circular economy, eco-friendly packaging innovation, and recycling technologies. The implementation of accounting standards such as PSAK 1, PSAK 16, PSAK 57, and PSAK 68 is crucial in ensuring transparency and accountability of environmental management. This study analyzes how these standards support the management of environmental obligations in the FMCG sector. The results show that the adoption of PSAK not only improves the transparency of financial reports but also drives the reduction of waste and carbon emissions. Sustainability reports based on PSAK improve corporate reputation and consumer trust. However, environmental regulations in Indonesia, such as Presidential Regulation No. 83 of 2018 and Law No. 32 of 2009, are still weak in implementation and enforcement, thus hampering investment in green technology. The lack of supervision worsens the situation, making companies less compliant with financial reporting and environmental responsibilities. This study recommends strengthening regulations, law enforcement, and adoption of international standards to encourage compliance and sustainability in the FMCG sector. The combination of innovation, PSAK compliance, and social commitment is the key to long-term sustainability.